Quantifying factory-scale CO2/CH4 emission based on mobile measurements and EMISSION-PARTITION model: cases in China. (2nd March 2023) - Shi, Tianqi; Han, Ge; Ma, Xin; Mao, Huiqin; Chen, Cuihong; Han, Zeyu; Pei, Zhipeng; Zhang, Haowei; Li, Siwei; Gong, Wei
Abstract: Development of the measurement-based carbon accounting means is of great importance to supplement the traditional inventory compilation. Mobile CO2 /CH4 measurement provides a flexible way to inspect plant-scale CO2 /CH4 emissions without the need to notify factories. In 2021, our team used a vehicle-based monitor system to conduct field campaigns in two cities and one industrial park in China, totaling 1143 km. Furthermore, we designed a model based on sample concentrations to evaluate CO2 /CH4 emissions, EMISSION-PARTITION, which can be used to determine global optimal emission intensity and related dispersion parameters via intelligent algorithm (particle swarm optimization) and interior point penalty function. We evaluated the performance of EMISSION-PARTITION in chemical, coal washing, and waste incineration plants. The correlations between measured samples and rebuilt simulated ones were larger than 0.76, and RMSE was less than 11.7 mg m −3, even with much fewer samples (25). This study demonstrated the wide applications of a vehicle-based monitoring system in detecting greenhouse gas emission sources.